Characterization and biological activities of polysaccharides extracted from the filamentous fungal cell wall: an updated literature review (Research, Society and Development, 2020)
Filamentous fungi are eukaryotic organisms with several industrial and pharmaceutical applications. Polysaccharides are the principal components of cell walls from Fungi and other organisms like diatoms, and have been reported in the industrial and medical fields as products with a huge number of different biological activities and applications. The objectives of this narrative review were to assess the characterization methods and and biological activities of polysaccharides extracted from the filamentous fungal cell wall. Glucans, chitin and galactomannans are the most common polysaccharide often found in the cell walls of fungi. These polysaccharides can contain different glycosidic linkage either an α or β-configuration and at various positions, such as (1-3,1-4, 1-6), as well as several molecular sizes. This leads to an almost limitless diversity in their structure and biological activity. There are many methods for polysaccharides characterization, among them; the methods commonly used involve Infrared Spectrometry (FT-IR), Nuclear Magnetic Resonance Spectroscopy (MRS), and gas chromatography-mass spectrometry (CG-MS). Typically, cell wall polysaccharides from filamentous fungi have been shown to possess complex, important and multifaceted biological activities including mainly antioxidant, anti-inflammatory, immunomodulatory, antinociceptive, antitumor and hypoglycemic activities. Due to the large number of filamentous fungi genus and species capable of producing useful polysaccharides, perform scientific researches, and produce novel scientific knowledge and information are particularly interesting in order to identify polysaccharides with potential biological activity and that can be used for medicinal purposes.